Intratumoral Fusobacterium nucleatum levels predict therapeutic response to neoadjuvant chemotherapy in esophageal squamous cell carcinoma - Yamamura, Kensuke (Clin Cancer Res, 2019)
PURPOSE: Emerging evidence indicates that gut microbiome plays a crucial role in the cancer pathogenesis. Although Fusobacterium nucleatum (F. nucleatum) is associated with poor prognosis in multiple cancers, its clinical significance in predicting response to chemotherapy in patients with esophageal squamous cell carcinoma (ESCC) remains unclear. EXPERIMENTAL DESIGN: The F. nucleatum levels were quantified by qPCR assays in tumor tissues from 551 ESCC patients from two independent cohorts, including 101 patients who received neoadjuvant chemotherapy prior to curative resection. Associations between F. nucleatum burden and recurrence free survival (RFS), as well with chemotherapeutic response were evaluated using response evaluation criteria in solid tumors (RECIST), primary tumor metabolic response defined by maximum standardized uptake value (SUVmax) changes in positron emission tomography - computed tomography (PET/CT), and pathological tumor regression grade (TRG). RESULTS: High burden of F. nucleatum in ESCC patients associated with poor RFS in both training (log-rank p=0.02; Hazard Ratio [HR]=1.61; p=0.03) and validation cohorts (log-rank p=0.003; HR=1.96; p=0.004). Importantly, ESCC patients with high levels of F. nucleatum displayed poor chemotherapeutic response for all three evaluation methods: RECIST (p=0.04), SUVmax change in PET/CT (p=0.0004), and TRG (p=0.003). CONCLUSIONS: We conclude that high levels of intratumoral F. nucleatum have a prognostic significance for predicting poor RFS in ESCC patients. More importantly, our data indicates that higher F. nucleatum burden correlates with poor response to neoadjuvant chemotherapy, suggesting the possibility that an antibiotic intervention against this bacterium may significantly improve therapeutic response in ESCC patients.